2001
DOI: 10.1002/path.998
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the presence of oncogenic HPV DNA assessed by polymerase chain reaction and Ki‐67 immunoquantitative features in cervical intraepithelial neoplasia

Abstract: The aims of this study were firstly to determine which Ki-67 immunoquantitative parameters correlate with the presence of oncogenic human papillomavirus (HPV) in cervical intraepithelial neoplasia (CIN) lesions; and secondly to compare prospectively the routinely assessed CIN grades with the Ki-67 quantitative pathological CIN grade, the expert revised grade, and the presence of oncogenic HPV DNA. HPV polymerase chain reaction (PCR) and Ki-67 immunoquantitation were performed on 90 consecutive biopsies (16 CIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1
3

Year Published

2003
2003
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 21 publications
1
18
1
3
Order By: Relevance
“…Interobserver differences in the classification of CIN grades are substantial even among well-trained observers, especially for less severe grades (13). Ki-67 quantitative image analysis has good reproducibility and could be used as a diagnostic support method for grading, especially in a research setting (11,12,14). We cannot exclude grading variability in the biopsy interpretation in this study, but this probably was not a significant factor because progression rates in the current study were similar to those in many international studies (2).…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Interobserver differences in the classification of CIN grades are substantial even among well-trained observers, especially for less severe grades (13). Ki-67 quantitative image analysis has good reproducibility and could be used as a diagnostic support method for grading, especially in a research setting (11,12,14). We cannot exclude grading variability in the biopsy interpretation in this study, but this probably was not a significant factor because progression rates in the current study were similar to those in many international studies (2).…”
Section: Discussioncontrasting
confidence: 59%
“…Earlier studies have shown that Ki-67 immunoquantitation is a sensitive marker of grade, presence or absence of oncogenic HPV, and possibly, biological behavior (11,12). We also found that quantitative image analysis obtains the most reliable and best predictive results of these CIN characteristics.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…19 20 88 Figure 6 shows the quantitative image analysis method. The combination of the Stratification Index (SI, which indicates, how high Ki-67positive nuclei are located in the epithelium; the higher the SI, the higher the CIN grade) and the number of Ki-67positive nuclei per 100 mm basal membrane (the more Ki-67positive nuclei, the higher the grade) is the best discriminating set of features that distinguishes the three CIN grades at the same time (fig 7).…”
Section: Ki-67 and Cin Gradementioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20] Without doubt, p16 and Ki-67 are the most widely available, robust, stable and strong predictive biomarkers currently available for handling CIN lesions. (The antibody MIB-1 is often used in paraffin wax sections to assess Ki-67 expression.…”
mentioning
confidence: 99%